Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content: 1. A pragmatic study of directive speech acts in the cartoon “Sadaqa Rasoul Allah” Prof. Asem Hehadeh Ali, Prof. Mohammad Ahmad Alqudah, Mrs. Mawaddah Mohd Zaki 2. Textual coherence in Surat At-Takwir Through a conscientious referral - A textual study Dr. Hamad Abdullah Hamad Al-Saif 3. The semantic orientation of the Qur’anic witness in Mughni al-Labib, between Ibn Hisham and the commentators, Bab al-Ain as a model Dr. Salman Saud Muslim Albalawi 4. Calculation of sentences between Arabic and Hebrew, models and comparisons Mr. Salameh Saleem Salameh Oudeh, Dr. Ahmed Hamed, Dr. Adel Shaqour 5. The Influence of Followed Nouns Dr. Bahiya Ahmad Abdullah Daoud, Prof. Mohammad Ali Younos Rabba 6. The Village in Al-Ashmawi’s Diwan of (The Basil Vendor) Mrs. Mrwa Mokhtar Elgheity 7. Parallel text in the Arabic novel (selected models) Mrs. Ahlam Maze Bakri, Co-Prof. Nadir Qasim